2022
DOI: 10.1021/acs.inorgchem.1c03688
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Magnetocaloric and Thermal Expansion Properties of the Ln3(adipate)4.5(DMF)2 (Ln = Gd–Er) Framework Series

Abstract: The development of sustainable and efficient cryogenic cooling materials is currently the subject of extensive research, with the aim of relieving the dependence of current low-temperature cooling methods on expensive and nonrenewable liquid helium. One potential method to achieve this is the use of materials demonstrating the magnetocaloric effect, where the cycling of an applied magnetic field leads to a net cooling effect due to changes in magnetic entropy upon application and removal of an external magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…91 This method allowed us to characterize the MCE for a higher ΔB of 5-0 T. The maximum magnetic entropy change obtained was −ΔS m (5 T) = 5.92 J K −1 kg −1 (mCB-Dy) and 5.55 J K −1 kg −1 (mCB-Tb). The magnetic entropy change values for these compounds are smaller than that previously obtained for the gadolinium (S = 7/2) analogue of the same family, mCB-Gd, which exhibited a value of −ΔS max m = 16.23 J kg −1 K −1 at T = 0.8 K for ΔB = 2 T. 92 However, interestingly, the MCE peak for the Dy and Tb MOFs occurs at a higher temperature than for Gd, consistent with previous findings in the literature, [51][52][53] thus extending the operating…”
Section: Papersupporting
confidence: 88%
“…91 This method allowed us to characterize the MCE for a higher ΔB of 5-0 T. The maximum magnetic entropy change obtained was −ΔS m (5 T) = 5.92 J K −1 kg −1 (mCB-Dy) and 5.55 J K −1 kg −1 (mCB-Tb). The magnetic entropy change values for these compounds are smaller than that previously obtained for the gadolinium (S = 7/2) analogue of the same family, mCB-Gd, which exhibited a value of −ΔS max m = 16.23 J kg −1 K −1 at T = 0.8 K for ΔB = 2 T. 92 However, interestingly, the MCE peak for the Dy and Tb MOFs occurs at a higher temperature than for Gd, consistent with previous findings in the literature, [51][52][53] thus extending the operating…”
Section: Papersupporting
confidence: 88%
“…The addition of fluoro-bridging in the cluster further decreases the distance between metal ions as the metal-fluoride bond is on average shorter than the metal–oxygen bond. , There have been several studies on how the addition of fluoro-bridging within lanthanide complexes changes the magnetic coupling between the lanthanide ions. , Additionally, clusters increase the concentration of the metal ions and help increase the overall magnetic susceptibility of the MOF . In this regard, the Gd 3+ , Tb 3+ , and Dy 3+ ions possess the highest magnetic moments among lanthanides and typically allow realization of interesting magnetic properties in various molecule-based materials. …”
Section: Introductionmentioning
confidence: 99%
“…Recently however, a number of materials have been reported that retain promising magnetocaloric properties up to 10 K through exploiting magnetic frustration arising from 1D chains of Ising spins within the crystal structure. 14,28–35…”
Section: Introductionmentioning
confidence: 99%
“…Recently however, a number of materials have been reported that retain promising magnetocaloric properties up to 10 K through exploiting magnetic frustration arising from 1D chains of Ising spins within the crystal structure. 14,[28][29][30][31][32][33][34][35] Currently, materials that maintain favourable magnetocaloric properties at temperatures above 10 K are much less common. In most cases, magnetic entropy changes and hence, magnetocaloric performance, decrease with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%